Penerapan Safety Talk Sebagai Upaya Pencegahan Kecelakaan Kerja di Pabrik Kelapa Sawit (PKS) Bunut PT. Perkebunan Nusantara VI Jambi 2022 - Girsang, Tania Peniela; Aswin, Budi; Sitanggang, Hendra Dhermawan (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2023)
K3 promotion through safety talk program aims to convey the message of occupational safety and health (OSH) in the workplace. As written in PP No. 50 of 2012 related to the implementation of SMK3, K3 communication through the safety talk program is one of the supporting components of work accident prevention efforts. Method of the research was conducted qualitatively using an in-depth interview and observation approach. There were 8 research informants consisting of 3 key informants, namely the management and 5 main informants, namely operators at each PKS Bunut processing station, PTPN VI Jambi. The results showed that the implementation of safety talk at PKS Bunut has been carried out quite well and the majority of employees already know the purpose of implementing safety talk. This is supported by the successful implementation of safety talk which is marked by a decrease in the number of work accidents in recent years. However, in its implementation, there are obstacles in how to communicate between leadership employees and implementing employees, as well as employee awareness and concern which are challenges in implementing safety talk at PKS Bunut. The implementation of safety talk at PKS Bunut has been carried out regularly and well. In the implementation process, there are several things that must be improved from the side of employees, leaders and implementing employees so that existing obstacles and challenges can be overcome and the successful implementation of safety talk can be achieved as an effort to prevent work accidents at PKS Bunut. Keywords: safety talk, application, work accident